Inhibitory hippocampus-medial septum projection controls locomotion and exploratory behavior - Chen, Yuh-Tarng; Arano, Rachel; Guo, Jun; Saleem, Uzair; Li, Ying; Xu, Wei (Frontiers in Synaptic Neuroscience, 2023)
Although the hippocampus is generally considered a cognitive center for spatial representation, learning and memory, increasing evidence supports its roles in regulating locomotion. However, the neuronal mechanisms of hippocampal regulation of locomotion and exploratory behavior remain unclear. Here we found that the inhibitory hippocampal synaptic projection to the medial septum (MS) bi-directionally controls locomotor speed of mice. Activation of the MS-projecting interneurons in the hippocampus, or activation of the hippocampus-originated inhibitory synaptic terminals in the MS, decreased locomotion and exploratory behavior. On the other hand, inhibition of the hippocampus-originated inhibitory synaptic terminals in the MS increased locomotion. Unlike the septal projecting interneurons, activation of the hippocampal interneurons projecting to the retrosplenial cortex did not change animal locomotion. Therefore, this study reveals a specific long-range inhibitory synaptic output from the hippocampus to the medial septum in the regulation of animal locomotion.